An approach to methodology and implementation of a Network Monitoring Analysis Tool - Christos Bouras; Petros Ganos; E Aravantinos; A Ilias (EUROMEDIA 2003 – COMTEC, Plymouth, UK, 2003)
In this paper we describe the design and implementation of a network monitoring analysis tool. The network resources were configured to support SNMP under various operating systems, thresholds definitions and events. The data were collected by a network monitoring system and handled according to the values of the variables or the event type. A real- time report to a database was established via adaptive scripts. A Network Node Manager (NNM) will inform an external, remote database about the network status by sending real time data containing alerts and events. The whole tool is called Network Management Analysis Tool (NMAT).